BIBLIOMETRIC ANALYSIS ON THE USE OF ARTIFICIAL INTELLIGENCE IN THE BANKING SECTOR (Third Sector Social Economic Review, 2025)
It is known that knowledge and technology bring innovations. However, the existence of technologies that learn and exhibit human-specific behaviors with artificial intelligence today seems to go beyond providing innovation. It is predicted that this innovation will deeply affect socioeconomic life. In fact, it is said that many of today's professions will not exist in the second half of the 21st century. Today, many sectors from health to industry tend to adapt to the process by using artificial intelligence intensively. It is also observed that the use of artificial intelligence is increasing especially in the finance sector. This study aims to systematically evaluate the literature on the increasing use of artificial intelligence in the banking sector and to examine the development process. For this purpose, a search was made using the terms “banking” and “artificial intelligence” in the Web of Science database. Only research articles were preferred and in this context, the data consists of 407 studies. Bibliometrix and VOSviewer applications were used in the analysis of these studies and the visualization of relationship networks. In the examined studies, analyses were made regarding authors, keywords, citation status, countries, references, prominent and high-impact study topics. As a result of the study, it was determined that issues such as deficiencies in legal regulations, financial engineering, identity verification, robo-advisory, perceived risk of using artificial intelligence applications, digital competence, etc. came to the fore in publications on banking and artificial intelligence. The study recommends conducting new research on issues such as evaluation, adoption, perceived benefit, etc. of artificial intelligence applications from the user perspective.
Keywords: Banking; Artificial Intelligence; Bibliometric Analysis; VOSviewer; Bibliometrix